The Marital Rape Phenomenon as A Form of Gender Oppression: An Analysis of the Urgency of Sexual Consent MubÄdalah's Perspective - Zakiah, Ade Rosi Siti; Nasiruddin, Muhammad; Naf'an, Abdul Wahab; Andania, Ruqoyyah Amilia (HUMANISMA : Journal of Gender Studies, 2023)
Many women continue to face cases of sexual abuse in biological relationships between husband and wife, sometimes known as marital rape. This phenomenon is often considered taboo to be discussed, conveyed, and addressed. So in turn, the phenomenon of marital rape becomes a problem that cannot be resolved immediately. In particular, the main question in this research is how Islamic law views the phenomenon of marital rape in husband-and-wife relations and whether the urgency of sexual consent from the mubadalah perspective is a step to prevent marital rape. This research is included in the category of library research with a qualitative approach, data collection techniques with documentation types, data processing techniques with descriptive-analytic methods, and an analytical framework with mubÄdalah theory. The results of this study show that the act of marital rape due to unequal sexual relations between husband and wife is part of an act of violence, both physically and psychologically. Islam prohibits sexual intercourse through coercion and violence. Husband-wife relationships in any condition must have an element of pleasure from each party, meaning that there should be no coercion from both. Thus, sexual consent education needs to be pursued to become a preventive spirit and safe behaviour for instilling a foundation of mutual respect between individuals. This is expected to pave the way for married couples to enjoy a healthy and happy relationship for both parties.masih banyak dialami oleh perempuan. Fenomena ini sering dianggap tabu untuk dibicarakan, disampaikan dan disikapi. Sehingga pada gilirannya fenomena marital rape menjadi permasalahan yang tidak segera ditanggulangi. Secara spesifik, pertanyaan utama dalam penelitian ini ialah bagaimana hukum Islam memandang fenomena marital rape dalam hubungan suami istri dan bagaimana urgensi sexual consent perspektif mubadalah sebagai upaya preventif terjadinya martial rape. Kajian ini termasuk pada kategori penelitian kepustakaan dengan pendekatan kualitatif, teknik pengumpulan data jenis dokumentasi, teknik pengolahan data dengan metode deskriptif-analisis, dan kerangka analisa dengan teori mubÄdalah. Hasil dari penelitian ini adalah bahwa tindakan marital rape akibat hubungan seksual yang tidak seimbang antara suami istri merupakan bagian dari tindakan kekerasan, baik secara fisik maupun psikis. Islam melarang hubungan seksual dengan paksaan dan kekerasan. Hubungan suami istri dalam kondisi apapun harus ada unsur kesenangan dari masing-masing pihak, artinya tidak boleh ada unsur paksaan dari keduanya. Dengan demikian, pendidikan sexual consent perlu diupayakan guna menjadi semangat preventif dan safe behaviour dalam menanamkan landasan saling menghargai antar individu. Hal ini diharapkan mampu membuka jalan untuk pasangan suami istri agar dapat menikmati hubungan yang sehat dan membahagiakan bagi kedua belah pihak.